Α-calcium sulfate hemihydrate with a 3D hierarchical straw-sheaf morphology for use as a remove Pb2+ adsorbent. (January 2022) - Zhang, Genlei; Cao, Dongjie; Wang, Xianshun; Guo, Shiyu; Yang, Zhenzhen; Cui, Peng; Wang, Qi; Dou, Yan; Cheng, Sheng; Shen, Hao
Abstract: Novel three-dimensional hierarchical α-calcium sulfate hemihydrate with a straw-sheaf morphology (3D α-HH straw-sheaves) are synthesized successfully in glycerin aqueous solution by a simple one-pot method, using as an efficient adsorbent for Pb 2+ removal from water. The 3D straw-sheaf morphology, that closely depends on the glycerin/water volume ratio (VGly /VH2O ), can be accurately fabricated only when VGly /VH2O is not lower than 3/1. 3D α-HH straw-sheaves are generated via multistep-splitting growth coupled with self-assembly. The obtained 3D α-HH straw-sheaves are further used as an adsorbent to remove Pb 2+ from water, exhibiting excellent Pb 2+ removal performance with an equilibrium adsorption capacity of 79.19 mgPb gα-HH −1 and removal efficiency of 98.98%, that both higher than those of plate- and columnar-like α-HH. Moreover, the experimental adsorption data for the 3D α-HH straw-sheaves is well fitted with pseudo-second-order kinetic model, and the adsorption isotherm is in good agreement with Langmuir model. The Pb 2+ adsorption mechanism is thought to be a chemical adsorption process enforced by chemical bonding and ion exchange. This work demonstrates that 3D α-HH straw-sheaves are highly promising in removing Pb 2+ from wastewater, thereby broadening the research field for the practical application of gypsum-based materials. Graphical abstract: Image 1 Highlights: A method to successfully synthesize 3D α-HH straw-sheaves was proposed. The formation mechanism of the straw-sheaf was analyzed. The excellent ability of 3D α-HH straw-sheaves to remove Pb 2+ from the water was confirmed. The Pb 2+ removal was mainly driven by both chemical bonding and ion exchange.